You need to factor out `e^(2x)` to denominator such that:

`int (dx)/(e^(2x)(e^(-x) + 1)) = int (e^(-2x))/(e^(-x)+1)dx`

You should use the following substitution such that:

`e^(-x) + 1 = t => -e^(-x)dx = dt`

`e^(-x) = t - 1`

Changing the variable yields:

`int (e^(-2x))/(e^(-x)+1)dx = int (e^(-x))/(e^(-x)+1) (e^(-x)dx) =int...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to factor out `e^(2x)` to denominator such that:

`int (dx)/(e^(2x)(e^(-x) + 1)) = int (e^(-2x))/(e^(-x)+1)dx`

You should use the following substitution such that:

`e^(-x) + 1 = t => -e^(-x)dx = dt`

`e^(-x) = t - 1`

Changing the variable yields:

`int (e^(-2x))/(e^(-x)+1)dx = int (e^(-x))/(e^(-x)+1) (e^(-x)dx) =int (t - 1)/t dt `

Using the property of linearity yields:

`int -(t - 1)/t dt = -int t/t dt+ int 1/t dt`

`int -(t - 1)/t dt = -int dt+ int 1/t dt`

`int -(t - 1)/t dt = -t+ ln|t| + c`

Substituting back `e^(-x) + 1` for t yields:

`int (dx)/(e^(2x)(e^(-x) + 1)) =-(e^(-x) + 1)+ ln(e^(-x) + 1) + c`

**Hence, evaluating the given indefinite integral yields `int (dx)/(e^(2x)(e^(-x) + 1)) = -(e^(-x) + 1) + ln(e^(-x) + 1) + c.` **